Sputum Smear Conversion as Prognostic Determinant of Timely Complete Therapy on Pulmonary Tuberculosis - Bastiana Bastiana; Muzaijadah Retno Arimbi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Tuberculosis (TB) remains a major health problem worldwide. The bacteriological diagnosis of TB is confirmed by a sputum smear, which shows a positive result. Sputum culture conversion at two months of TB therapy has a higher possibility of completing therapy; however, this method is time-consuming and expensive. This study aimed to analyze the initial smear and smear conversion of sputum in the intensive phase therapy as a prognostic determinant of appropriate time-targeted therapy. This was a retrospective study on pulmonary TB patients collected from January 2016 to December 2017. The research subjects at the beginning of the intensive phase were divided into Acid-Fast Bacilli (AFB)-negative and AFB-positive (1+, 2+, 3+) sputum smears. The sputum smear examination was evaluated at the end of the intensive phase and the end of the six-month treatment. The pulmonary TB patients in this study were 430 patients, dominated by males with the main distribution age of 45-54 years. At the beginning of the intensive phase, the negative results of the AFB examination were 85.4% and the total positive results with 1+, 2+, or 3+ were 14.6%. At the end of the intensive phase, the sputum smear examination of all patients showed 100% conversion, and the sputum smear examination at the end of six months of treatment showed negative results. This study has revealed that sputum conversion at the end of the 2-month intensive phase can be used as a prognostic determinant of timely complete therapy on pulmonary tuberculosis.